FUNGICIDAL POTENTIAL OF FLOWER EXTRACT OF CASSIA FISTULA AGAINST MACROPHOMINA PHASEOLINA AND SCLEROTIUM ROLFSII - M. F. H. Ferdosi; H. Ahmed; I. H. Khan; A. Javaid (Journal of Animal and Plant Sciences, 2022)
Macrophomina phaseolina and Sclerotium rolfsii are the two important soil-borne phytopathogens causing diseases in hundreds of plant species. In search of alternatives to synthetic fungicides, the present study was carried out to investigate the antifungal activity of methanolic extract of flowers of Cassia fistula L. against these two highly destructive plant pathogens. The extract was prepared by soaking 200 g shade dried flowers of the test plant species in 1000 ml of methanol for two weeks, followed by filtration and evaporation on a rotary evaporator. Bioassays carried out with 1.562, 3.125, 6.250, 12.500, 25.000, and 50.000 mg/ml concentrations of the extract exhibited 2–36% and 31–56% reduction in biomass of M. phaseolinaand S. rolfsii, respectively. The extract was partitioned with n-hexane followed by chloroform and the later fraction was analyzed by GC-MS that showed presence of 37 compounds. Hexacosane (16.06%) followed by heptacosane (10.94%) and benzene, 1,2,3-trimethyl- (8.12%) were recognized as the principal components of chloroform fraction. Compounds namely heptadecane (7.15%), benzene, 4-ethyl-1,2-dimethyl- (4.60%), benzene, 1,2,3,4-tetramethyl- (3.93%), benzene, 2-ethyl-1,4-dimethyl- (3.88%), aniline, N-methyl- (3.68%) and naphthalene (3.08%) were ranked as moderately abundant. Some of the identified compounds are known to possess antifungal activities against various fungal species and could be responsible for antifungal activity of the flower extract against M. phaseolina and S. rolfsii in the present study. This study also concluded that S. rolfsii was more susceptible to the flower extract than M. phaseolina.
Keywords: Antifungal; Cassia fistula; Flower extract; GC-MS analysis